Bi the Way: Rethinking Categories of Religious Identity - Ursic, Elizabeth (The international journal of religion and spirituality in society, 2014)
A single category of religious identification no longer serves a significant and growing segment of the U.S. population. The percentage of people describing themselves using a single religious term such as "Lutheran", "Jewish", or "Hindu" is shrinking. Identification by religious affiliation no longer reflects how many Americans view the complexity of their religious beliefs and practices. Younger generations in particular are identifying with broader, more general terms such as "spiritual" or "spiritual but not religious". Despite these trends, the field of religious studies continues to use religious affiliation as its primary way to categorize religious identification. In contrast, the discipline of gender studies has worked for more than half a century to re-conceptualize how gender is defined and categorized. This article explores what type of religious studies research might be generated if concepts from gender studies such as bi and trans were also used to investigate new patterns of religious identification.